2005
DOI: 10.1002/chem.200500004
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Dimensional Organization of Helices: Design Principles for Nucleobase‐Functionalized β‐Peptides

Abstract: The construction and molecular recognition of various three-dimensional biomimetic structures is based on the predictable de novo design of artificial molecules. In this regard beta-peptides are especially interesting, since stable secondary structures are obtained already with short sequences; one of them is the 14-helix in which every third residue has the same orientation. The covalent functionalization of every third 14-helix side chain with nucleobases was used for a reversible organization of two helices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
50
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 74 publications
3
50
0
Order By: Relevance
“…As a synthetic route to an easily variable spacer backbone, we used solid phase peptide synthesis procedures [17].The most prominent advantages of proposed approach are: a) an easy preparation of novel amino acid-phenanthridine monomer; b) oligomerisation of monomers can be easily controlled by means of order, chirality of linker, distance between monomers; c) simple and fast preparation of new generations of compounds by modification of the last (oligomerisation) step.…”
Section: Resultsmentioning
confidence: 99%
“…As a synthetic route to an easily variable spacer backbone, we used solid phase peptide synthesis procedures [17].The most prominent advantages of proposed approach are: a) an easy preparation of novel amino acid-phenanthridine monomer; b) oligomerisation of monomers can be easily controlled by means of order, chirality of linker, distance between monomers; c) simple and fast preparation of new generations of compounds by modification of the last (oligomerisation) step.…”
Section: Resultsmentioning
confidence: 99%
“…[9] Through observation of the packing of the secondary structural units in the solid state, tertiary structural motifs potentially available for b-peptides were identified; Xray crystallographic studies revealed a H14 helix-bundle motif [10] and a polar pleated sheet. [3] As a further step towards tertiary structures, designed b-peptide helices have been observed to exhibit self-association in solution, [11][12][13][14] but the creation of distinct tertiary structures with specific morphologies still remains a challenge.…”
mentioning
confidence: 99%
“…In addition, β-peptide 3 14 -helices furnish an ideal structural backbone for the well-organized presentation of recognition units since incorporation of artificial β-amino acids allows positioning of side chains on one side of the helix in equidistant 5 Å intervals. This concept was proven to be beneficial for base-pair recognition of β-peptide nucleic acids leading to high duplex stabilities of entropically preorganized recognition units [1517]. Further, the presentation of a sugar unit on a β-peptide helical topology was reported by Arvidsson and coworkers [1819].…”
Section: Introductionmentioning
confidence: 99%